For positive integers a and b that satisfy ( 3 6 + 1 ) ( 3 6 2 + 1 ) ( 3 6 4 + 1 ) ( 3 6 8 + 1 ) = b 6 a − 1 , what is the value of a + b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
WOW!!! very interesting solution...
thank u
good solution
I did it by using gp series formula after multiplying it fully
We can use the equation ( a − b ) ( a + b ) = a 2 − b 2 .First,we multiply both sides by ( 3 6 − 1 ) = 3 5 to get
( 3 6 − 1 ) ( 3 6 + 1 ) ( 3 6 2 + 1 ) ( 3 6 4 + 1 ) ( 3 6 8 + 1 ) = b 6 a − 1 × 3 5
By multiplying the terms on the left hand side,we get
( 3 6 2 − 1 ) ( 3 6 2 + 1 ) ( 3 6 4 + 1 ) ( 3 6 8 + 1 ) = b 6 a − 1 × 3 5
= ( 3 6 4 − 1 ) ( 3 6 4 + 1 ) ( 3 6 8 + 1 ) = b 6 a − 1 × 3 5
= ( 3 6 8 − 1 ) ( 3 6 8 + 1 ) = b 6 a − 1 × 3 5
= 3 6 1 6 − 1 = b 6 a − 1 × 3 5
Because 3 6 = 6 2 , 3 6 1 6 = ( 6 2 ) 1 6 which is equal to 6 3 2 since ( 6 2 ) 1 6 is equal to 6 2 × 6 2 × 6 2 . . . . . . . . . 16 times.So we have
6 3 2 − 1 = b 6 a − 1 × 3 5
The factors of 35 are 1,5,7 and 35.Because 6 3 2 − 1 is a positive integer , b must be 1,5,7 or 35 for b 6 a − 1 × 3 5 to be an integer.It is easy to observe that b 6 a − 1 × 3 5 is an integer of the form 6 a − 1 only if b = 3 5 ,so we have 6 3 2 − 1 = 3 5 6 a − 1 × 3 5 .After cancelling out the 35, we can find that a = 3 2 , so a + b = 3 2 + 3 5 = 6 7 .
out standing thank u
This can be written as (6^2 + 1) * (6^4 + 1) * (6^8 + 1) * (6^16 + 1) =
[(6^4 - 1)/(6^2 - 1)] * [(6^8 - 1)/(6^4 - 1)] * [(6^16 - 1)/(6^8 - 1)] * [(6^32 - 1)/(6^16 - 1)] =
(6^32 - 1) / (6^2 - 1) = (6^32 - 1) / 35. Thus a = 32, b = 35 and so a + b = 67.
(36+1)(36^2+1)(36^4+1)(36^8+1)=(36^16-1)/(36-1)=(6^32-1)/35 hence a=32, b=35 & a+b=67
Problem Loading...
Note Loading...
Set Loading...
Rewrite ( 3 6 + 1 ) ( 3 6 2 + 1 ) ( 3 6 4 + 1 ) ( 3 6 8 + 1 ) = ( 6 2 + 1 ) ( 6 4 + 1 ) ( 6 8 + 1 ) ( 6 1 6 + 1 ) = ( 6 2 − 1 ) ( 6 4 − 1 ) ⋅ ( 6 4 − 1 ) ( 6 8 − 1 ) ⋅ ( 6 8 − 1 ) ( 6 1 6 − 1 ) ⋅ 6 1 6 − 1 6 3 2 − 1 ⋅ = ( 6 2 − 1 ) 6 3 2 − 1 = 3 5 ( 6 3 2 − 1 ) . Thus, a = 3 2 , b = 3 5 , and a + b = 6 7 . # Q . E . D . #